Medical Research Conduct and Publication during Higher Education in Syria: Attitudes, Barriers, Practices, and Possible Solutions - Hanafi, Ibrahem; Haj Kassem, Luma; Hanafi, Mouaz; Ahmad, Sulafa; Abbas, Ola; Hajeer, Mohammad Younis; Alsalkini, Marah; Alahdab, Fares (Avicenna Journal of Medicine, 2022)
Background: The huge workload on doctors especially residents, who are the main health care providers in public hospitals, in addition to the vanishing incomes and lack of personal safety during the decade-long Syrian crisis, led to further hurdles in the focus on research. Postgraduate students in the medical and paramedical fields must conduct original research projects as part of their graduation requirements. However, this does not reflect on research publications coming from Syria.Methods: This is a nation-wide cross-sectional study targeting medical, dental, and pharmacy postgraduate students who are at the phase of planning for their required projects. The questionnaire aimed to capture their attitudes toward research, perceived barriers, and previous research experiences in order to suggest evidence-based recommendations.Results: The sample consisted of 429 residents representing about 22% of the target population. Nearly all the participants had positive opinion toward the important role of medical research and the significance of their participation. Agreement was also clear regarding perceived barriers, including the lack of adequate training and research facility. Seventy-one percent of the participants were not involved in any research before the time of their master theses, less than 13% of them had submitted an article for publication, and less than 5% had submitted more than one paper. Despite that, high-quality internet connectivity and rich English writing skills were associated with further research experiences. Additionally, mentors' support and self-paced learning of research skills had significant positive impact on students' research contributions with odds ratios of 2.04 [[95% Confidence Interval]: 1.02–4.06] and 2.68 [1.48–4.84], respectively.Conclusion: Lack of training and mentorship, in addition to several common barriers to medical research, hampered residents' capacity of conducting and publishing research despite their positive attitudes toward it. Nevertheless, the variance within our sample exposed a promising window for implementing low-cost institutional and individual solutions such as peer-run self-paced training opportunities and long-distance mentoring.
Keywords: research contributions; publication practices; postgraduate students; Syrian crisis; residents' attitudes; institutional barriers